IDN 5390: an oral taxane candidate for protracted treatment schedules - Pratesi, G (Nature Publishing Group, 2003)
The recognition of the antiangiogenic properties of taxanes provides a basis for novel therapeutic approaches. A prolonged exposure to low drug concentrations has been proposed to be the most suitable approach to exploit the antiangiogenic potential of cytotoxic agents. Such schedule is required to target preferentially slowly dividing endothelial cells. The protracted use of taxanes could benefit from the availability of a taxane endowed with a favourable tolerability profile. Among compounds of a novel series of C-seco taxanes, IDN 5390 was originally selected on the basis of its potent antimotility activity and poor cytotoxicity on endothelial cells. The aim of the study was to investigate the preclinical pharmacologic profile of IDN 5390 in a variety of human tumour xenografts, including ovarian and colon carcinoma and a glioblastoma. IDN 5390, delivered by s.c. injection, daily for 5 days per week, exhibited a high activity against all tumours investigated (tumour growth inhibition was always >85%) in the range of well-tolerated doses. The maximum tolerated dose/injection (MTD), with no signs of systemic or local vesicant toxicity, was 120 mg kg(−1). In contrast, paclitaxel, delivered according to the same schedule, exhibited a variable antitumour efficacy associated with a substantial local toxicity (MTD=10 mg kg(−1)). Considering the remarkable efficacy of IDN 5390 delivered s.c. by protracted treatment schedule, the oral route of administration was further investigated, as the most suitable for daily treatment. Indeed, a good bioavailability of oral IDN 5390 was found. Oral IDN 5390 maintained a substantial efficacy against human tumour xenografts, including paclitaxel-resistant tumours, without loss of potency with respect to s.c. administration. In conclusion, the therapeutic advantages of IDN 5390, over paclitaxel, in protracted daily treatment schedules are represented by the oral efficacy and the high tolerability, which are favourable features to exploit the antiangiogenic potential and to design combinations with other effective agents.